2017
DOI: 10.1016/j.annepidem.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain during pregnancy and the black-white disparity in preterm birth

Abstract: Purpose To quantify the relationship between pregnancy weight gain with early and late preterm birth and evaluate whether associations differed between non-Hispanic (NH) black and NH white women. Methods We analyzed a retrospective cohort of all live births to NH black and NH white women in the U.S. 2011-2015 (n = 10,714,983). We used weight gain z-scores in multiple logistic regression models stratified by prepregnancy body mass index (BMI) and race to calculate population attributable risk (PAR) percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…12 A few studies that assessed gestational weight gain and preterm birth in relation to race/ethnicity have reported modest and inconsistent differences between non-Hispanic black and white women. 17,18,21,30,31 In the current analysis, we extended our assessment of gestational weight gain and preterm birth to seven racial/ethnic groups. There were considerable differences in weight gain amounts and the prevalence of preterm birth among racial/ethnic groups; however, differences in the optimal ranges of gestational weight gain for minimal risk of preterm birth were small and do not substantiate tailoring weight gain recommendations to race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A few studies that assessed gestational weight gain and preterm birth in relation to race/ethnicity have reported modest and inconsistent differences between non-Hispanic black and white women. 17,18,21,30,31 In the current analysis, we extended our assessment of gestational weight gain and preterm birth to seven racial/ethnic groups. There were considerable differences in weight gain amounts and the prevalence of preterm birth among racial/ethnic groups; however, differences in the optimal ranges of gestational weight gain for minimal risk of preterm birth were small and do not substantiate tailoring weight gain recommendations to race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences prompted the IOM in 1990 to recommend that non‐Hispanic black women gain at the upper end of the recommended gestational weight gain ranges, but this recommendation was abandoned in the 2009 IOM revision because of insufficient evidence . A few studies that assessed gestational weight gain and preterm birth in relation to race/ethnicity have reported modest and inconsistent differences between non‐Hispanic black and white women . In the current analysis, we extended our assessment of gestational weight gain and preterm birth to seven racial/ethnic groups.…”
Section: Commentmentioning
confidence: 99%
“…Interpretation of weight gain z-scores may be less intuitive than absolute weight gain, so conversion of the z-scores back to kilograms (eg the number of kilograms corresponding to 0.2 weight gain z-score at 40 weeks') may be useful for presenting and discussing study findings. 20 The charts also require an assumption that the patterns of weight gain in the study population are similar to those of the population used to derive the chart. The recent publication of a weight gain chart from a global population (based on the INTERGROWTH 21st cohort) should help increase generalisability and comparability of studies across different jurisdictions.…”
Section: Weight-gain-for-gestational-age Z-scoresmentioning
confidence: 99%
“…Interpretation of weight gain z ‐scores may be less intuitive than absolute weight gain, so conversion of the z ‐scores back to kilograms (eg the number of kilograms corresponding to 0.2 weight gain z ‐score at 40 weeks’) may be useful for presenting and discussing study findings . The charts also require an assumption that the patterns of weight gain in the study population are similar to those of the population used to derive the chart.…”
Section: Characterising Gestational Weight Gain Using a Single Measurmentioning
confidence: 99%
“…In a meta-analysis study carried out with 10 171 obese preterm births in pregnant women with gestational weight gain over the indicated increased risk [32]. In another study it was found that gestational weight gain above the recommendations and moderate weight gain during pregnancy is associated with preterm [33,34]. In a study by Vivatkusol, et al, percentage of cesarean section was increased in the overweight and obese pregnant women; in contrast, the rate of preterm births showed an increase in underweight pregnant womens [35].…”
mentioning
confidence: 99%